Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species - Byun, Bong-Kyu (Zootaxa, 2006)
The family Alucitidae in Korea is reviewed. One species is described as new, Pterotopteryx koreana sp. nov., and two species are reported for the first time, Alucita japonica (Matsumura) and Pterotopteryx spilodesma (Meyrick). A key to the three species is provided, along with data on their biology and geographical distribution. External and genitalic characteristics of the species are described and illustrated.